Effect of shooting experience on executive function: differences between experts and novices - Shao, M.; Lai, Y.; Gong, A.; Yang ,Y.; Chen, T.; Jiang, C. (PeerJ, 2020)
Background: Executive function (EF) plays an important role in controlling human actions. Shooting is a closed motor skill, characterized by high anti-interference ability and high mental intensity. However, the beneficial effects of closed exercises such as shooting on EF remain unclear.